Genetically high angiotensin-converting enzyme concentrations causally increase asthma risk: A meta-analysis using Mendelian randomization - Hui, Qin; Hao, Ying; Ye, Fang; Pang, Bo; Niu, Wenquan; Zhang, Qi (Frontiers in Medicine, 2022)
Objectives: This meta-analysis aimed to test the association of angiotensin converting enzyme (ACE) gene I/D polymorphism with asthma risk and circulating ACE changes. Methods: Public literature retrieval, publication selection and information extraction were completed independently by two investigators. Effect-size values are expressed as odds ratio (OR) or standardized mean difference (SMD) with 95% confidence interval (95% CI). Results: Nineteen studies (2888 patients and 9549 controls) fulfilled eligibility criteria. Overall investigations demonstrated that ACE gene I/D polymorphism was significantly associated with asthma risk under allelic (OR, 95% CI: 1.26, 1.08 to 1.48), homozygous genotypic (1.50, 1.09 to 2.06), and recessive (1.53, 1.24 to 1.89) models, with moderate heterogeneity (I2 statistic: 64% to 79%). Subsidiary investigations recorded that race, matched status, asthma diagnosis, sample size and age possibly accounted for the existence of significant heterogeneity. Relative to carriers with the II genotype, those with the DD genotype, ID genotype and the combination of DD and ID genotypes had significantly higher concentrations of circulating ACE (WMD: 3.13, 2.07 and 2.83 U/L, respectively, p <0.05). Adoption of Mendelian randomization analyses revealed that one unit increment in circulating ACE concentrations was found to be significantly associated with 1.14-fold increased risk of asthma (95% CI: 1.02 to 4.24). Conclusions: We provided strong meta-analytical evidence supporting the causal implication of high circulating ACE concentrations in the development of asthma.